Steel Integrated IR Thermopile Array for Characterizing Grinding Processes. (2016) - Reimers, M.; Kolkwitz, B.; Beck, D.; Sarma, M.; Heinzel, C.; Lang, W.; Dumstorff, G.
Abstract: We present an infrared sensor array integrated in a steel workpiece to measure the local temperature distribution during a grinding process. The sensor is mounted in the workpiece in a way that the field of vision is 1mm next to grinding surface. We measure with 64 pixels over a 16x4mm surface on the level of the grinding surface. During grinding temperature in the field of vision is recorded. Grinding was performed with different grinding parameters to analyze the temperature distribution in the steel. The measurements show relatively low temperatures within the chosen parameters. The chosen approach is used to characterize the thermal material load which is expected to correlate with material modifications for higher temperature at high removal rate.